Methotrexate Toxic Effects on the Cerebellum and Vitamin C Protective Function - Hala Mohamed AlKhalidi; Shatha Shayan Almutairi; Ali Hassan A. Ali (International Journal of Biomedicine)
Background: The cerebellum, often referred to as the “little brain,” is primarily responsible for motor coordination and balance. However, recent research has shown that it also plays a role in a variety of cognitive processes, such as learning, attention, and even emotion regulation. This study aimed to evaluate how vitamin C might lessen the negative effects of methotrexate on the cerebellum of male albino rats. Methods and Results: The study included 30 healthy adult albino rats weighing between 200 g and 250 g. The animals were divided into three groups. Group 1 included 10 rats that did not receive medicine and were given distilled water orally and regularly. Group 2 included 10 rats given intraperitoneal injections of 10 mg/kg methotrexate once a week for 4 weeks. Group 3 included 10 rats given intraperitoneal injections of 10 mg/kg of methotrexate once a week for 4 weeks and 20 mg/kg of vitamin C via gastric gavage every other day for four 4 weeks. On the designated day, the animals were killed, and the cerebellum was removed and prepared for light microscopic analysis. In the methotrexate-treated group, the granular cell layer in the cerebellar layer was noticeably thinner than the molecular cell layer, which had significantly less cellularity. Purkinje cells lost their flask-shaped arrangement and mono-laminar configuration. Purkinje cells were irregular and shrunken, with several vacuolated patches between them and homogeneous, darkly pigmented cytoplasm and weak nuclei. In the methotrexate + vitamin C group, the thickness of the cerebellar cortex layers was better preserved, and the molecular layer displayed normal cellularity. Certain Purkinje cells had typical dimensions, shape, and organization, whereas other cells displayed uneven and homogenous cytoplasm, with less discernible vacuolated regions surrounding them. The molecular cell layer had greater cellularity, was regularly shaped, had more plentiful basket cells, and had no perineural gaps around them. Conclusion: Using vitamin C can lessen the toxicity of methotrexate, which is extremely toxic to the cerebellar cortex and destroys cortical cells, particularly granule cells and Purkinje cells.